2022
DOI: 10.3389/fenvs.2022.1040903
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ampicillin based on the fluorescence of a biocatalytic oxidation product

Abstract: Antibiotics used in humans and farmed animals are an essential source of water and soil contamination. Ampicillin is a micropollutant commonly found in water, sludge, food, flora, and fauna. However, the methods used for its detection in environmental samples are often complicated and expensive. Therefore, developing more straightforward strategies to detect well-known target antibiotics is necessary. In this context, enzyme-based detection methods have been demonstrated to be selective, sensitive, rapid, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
(38 reference statements)
0
1
0
Order By: Relevance
“… 7 Moreover, a high level of CIP has been reported from groundwater in South India, 12 while AMP was reported in water samples collected from the treatment plant's secondary effluent drinking water, river, groundwater, and lagoon water. 13 Recently, a study revealed high frequency (64.5% strains) of resistance to AMP in the Białka River discharge treatment resource. 14 Such contamination with AMP has a significant environmental impact that cannot be overlooked.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Moreover, a high level of CIP has been reported from groundwater in South India, 12 while AMP was reported in water samples collected from the treatment plant's secondary effluent drinking water, river, groundwater, and lagoon water. 13 Recently, a study revealed high frequency (64.5% strains) of resistance to AMP in the Białka River discharge treatment resource. 14 Such contamination with AMP has a significant environmental impact that cannot be overlooked.…”
Section: Introductionmentioning
confidence: 99%